PENGARUH GAYA KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PADA BIRO UMUM DI SEKRETARIAT JENDERAL DEWAN PERWAKILAN DAERAH REPUBLIK INDONESIA - Assofa Marwah; Erica, Denny (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2025)
A comfortable work environment and effective leadership play a big role in boosting employee performance. These two aspects support and complement each other. If both work well, employees will be encouraged to give their best and work responsibly, so that their performance increases and has a positive impact on the company. This research aims to analyze the influence of leadership style and work environment on the performance of General Bureau employees at the Secretariat General of the Regional Representative Council of the Republic of Indonesia. The methodology used is quantitative statistics by distributing questionnaires via Google Form. The population and sample for this study consisted of employees of the General Bureau at the Secretariat General of the Regional Representative Council of the Republic of Indonesia, totaling 70 respondents. Based on the hypothesis, this research was tested using the t test and F test. The research results showed that partially leadership style had a positive and significant influence on employee performance. This is indicated by the calculated t value of 2,485 > t table 1,668 with a sig value. 0.015. The work environment also partially has a positive and significant effect on employee job satisfaction, which is indicated by a calculated t value of 3,073 > t table 1,668 and a sig.0.003 value. Simultaneously, leadership style and work environment have a positive and significant effect on employee performance, with a calculated F value of 8,552 > F table 3,136 and a sig. 0,000.